Characterization of parotid gland tumors using T2 mapping imaging: initial findings. (May 2020) - Wu, Qian; Zhu, Liu-Ning; Jiang, Jia-Suo; Bu, Shou-Shan; Xu, Xiao-Quan; Wu, Fei-Yun
Background: Preoperative accurate characterization of parotid gland tumors in different histologic types is crucial. T2 mapping has been proven to be useful for improving the accuracy of tumor characterization. Purpose: To evaluate the ability of T2 mapping imaging in the characterization of parotid gland tumors. Material and Methods: T2 mapping imaging was scanned in 74 patients (56 benign, 18 malignant) with pathologically confirmed parotid gland tumors. Mean T2 relaxation time was calculated and compared between benign and malignant group, and among malignant tumors, Warthin's tumors, and pleomorphic adenomas. Independent-samples t test, one-way analysis of variance test, and receiver operating characteristic curve analyses were used for statistical analyses. Results: The malignant group showed significantly lower T2 relaxation times than the benign group ( P = 0.001). Using a relaxation time of 91.5 ms as the cut-off value, optimal diagnostic performance could be achieved (area under the curve [AUC] 0.679, sensitivity 46.4%, specificity 94.4%). Pleomorphic adenomas showed significantly higher T2 relaxation times than malignant tumors ( P = 0.003) and Warthin's tumors ( P = 0.001). However, no significant difference was found on the T2 relaxation times between Warthin's tumors and malignant tumors ( P = 0.435). Optimal diagnostic performance could be achieved (AUC 0.783, sensitivity 58.1%, specificity 94.4%), when setting a T2 value of 92.0 ms as the threshold value for differentiating pleomorphic adenomas from malignant tumors. Meanwhile, optimal AUC, sensitivity, and specificity were 0.892, 87.1%, and 83.3%, respectively, when setting a T2 value of 80.5 ms as the threshold value for differentiating pleomorphic adenomas from Warthin's tumors. Conclusion: T2 mapping imaging could serve as an incremental imaging biomarker for characterizing parotid gland tumors.